Characterisation of damage evolution in plain weave SiC/SiC composites using in situ X-ray micro-computed tomography. (1st November 2021) - Zhang, Daxu; Liu, Yu; Liu, Hailong; Feng, Yuqi; Guo, Hongbao; Hong, Zhiliang; Chen, Chao; Zhang, Yi
Abstract: The paper presents the investigation of microstructures and tensile damage evolution of plain weave SiC fibre reinforced SiC matrix (SiC/SiC) composites using X-ray computed tomography (CT). A miniature high-precision in situ X-ray CT test fixture has been developed to conduct micro X-ray CT in-situ tensile tests. Through the image reconstruction of the CT data, the actual microstructures and the damage evolution of the material under six successive loading levels have been revealed precisely. Deep-learning-based image segmentation has been employed to recognise material damages, including transverse matrix cracking, longitudinal matrix cracking, and fibre pull-outs. Three-dimensional rendering models of these damages have been created to quantify the damage initiation and evolution. Both transverse and longitudinal matrix cracking initiates and propagates gradually at the intermediate loading level, but rapidly at the high loading level. The volume fraction of longitudinal matrix cracks is much larger than that of its transverse counterpart. It indicates that the longitudinal matrix cracking is much severer damage than transverse tracking. The lengths of fibre pull-outs at the fracture surface of fibre tows are in a broad range and on average they are in the order of a hundred microns.